The effects of the hypothalamus on hemodynamic changes elicited by vagal nerve stimulation. - Niwa, H. (American Dental Society of Anesthesiology, 1996)
To investigate the means by which neurogenic shock or syncope occur in dentistry, we determined the hemodynamic response to the activation of vagal tone in cats while they were under emotional stress. The hypothalamus and the vagal nerve were electrically stimulated to produce emotional stress and to activate vagal tone, respectively. Hemodynamic changes were recorded during vagal stimulation (Va group) and during vagal stimulation preceded by hypothalamic stimulation (AH + Va group). Although blood pressure decreased in both groups, the degree of hypotensive response in the AH + Va group was greater than the response in the Va group. Total peripheral resistance (TPR) was reduced in the AH + Va group but was increased in the Va group. The blood flow to the skeletal muscles in the AH + Va group was greater than that of the Va group. Reduced TPR, which could be due to vasodilation in the skeletal muscles, was the cause of intensified hypotension in the AH + Va group. Clearly, the hypotension produced by vagal stimulation was worsened when it was preceded by hypothalamic stimulation; this occurrence could be related to the tendency of blood to flow to the skeletal muscles.